A Modified Disposable Circumcision Suture Device with Application of Plastic Sheet to Avoid Severe Bleeding After Circumcision - Li, Miao; Ang, Xiaojie; Chen, Weiguo; Gai, Nianxin; Xu, Jiangnan; You, Jiawei; Huang, Yuhua; Hou, Jianquan (Urology Journal, 2022)
Purpose: To evaluate the effectiveness of a modified disposable circumcision suture device (DCSD) with application of plastic sheet to avoid severe bleeding after circumcision and compare the surgical effects and other postoperative complications of two DCSDs. Materials and Methods: A total of 943 excess foreskin patients from January 2018 to January 2020 who underwent circumcision using two different DCSDs were recruited. Preoperative characteristics (patient age, height and weight), main surgical outcomes (surgical time, intraoperative blood loss, incision healing time) and postoperative complications (postoperative hemorrhage and hematoma rate, edema rate, incision infection rate, residual staples rate) were collected and analyzed. Patients’ "satisfaction" or "dissatisfaction" was also investigated. Results: Preoperative characteristics showed no significant statistical difference. The modified DCSD group has a lower intraoperative bleeding, postoperative hemorrhage or hematoma rate and residual staples rate compared with the conventional group. Incision healing time and incision infection rate between the two groups were similar. Nevertheless, conventional group has a shorter surgical time, a lower edema rate and a higher satisfaction rate. Conclusion: The modified DCSD with application of plastic sheet can avoid severe bleeding after circumcision effectively and can be served as a new choice for circumcision.